Isolation and antibiotic sensitivity of Aeromonas from children with diarrhea - Meiyanti, Meiyanti; Salim, Oktavianus Ch.; Surjawidjaja, Julius E.; Lesmana, Murad (Faculty of Medicine, Trisakti University, 2010)
Aeromonas species are gram-negative, motile, facultative anaerobic, rod shaped, oxidase positive bacteria of the recently assigned family Aeromonadaceae. The significance of Aeromonas species as causative agent of human diarrhoea has recently been established. The aim of the present study was to investigate the distribution, and antibiotic sensitivity of Aeromonas in nonhospitalized children with diarrhea.One hundred and seventeen rectal swabs from children with diarhhea were cultured for isolation of Aeromonas organisms as the etiological agents. In addition to Aeromonas, other enteric pathogens were also isolated. Overall, the isolates of enteric pathogens amounted to 36.8%, consisting of Salmonella, Shigella, Aeromonas, and Vibrio. Aeromonas was only found in 5.1% of cultures, with a ratio of A. caviae and A. hydrophila of 2:1, while Salmonella made up the majority of causative organisms with an isolation frequency of 18.8%, followed by Shigella with 11.1%. In this study no isolates of Vibrio cholerae O1 were found as etiological agents of diarrhea; however, V. cholerae non-O1 and V. parahaemolyticus were found in small numbers (<1%). All isolates of Aeromonas were resistant to ampicillin and tetracycline, but sensitive to ciprofloxacin and ceftriaxone, as were the other enteric pathogens. Although the frequency of isolation of these enteric pathogens was higher than for Vibrio spp., their role in infective diarrhea was less clearcut in comparison with Salmonella and Shigella.